1998
DOI: 10.1007/bf02303766
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant poxviruses to stimulate anti-melanoma T cell reactivity

Abstract: Human DC are receptive to infection by recombinant poxviruses encoding MAA genes and are capable of efficiently processing and presenting these MAA to cytotoxic T cells. The potential advantage of this approach is the ability to present specific antigen independent of the identification of the epitope or the MHC restriction element. This strategy may be useful for the identification of relevant epitopes for a diverse number of HLA alleles and for active immunization in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…7,8,27 In particular, we observed that this strategy was more efficient than the exogenous pulsing of iDC with saturating levels of relevant epitope. 7,8 The reason for the enhanced efficiency remained unclear, and we postulated that the longer persistence of Ag on the surface of DC due to the prolonged production of antigenic molecules driven by the viral promoters might have been responsible. 8 Surprisingly, however, in the conduct of these studies we noted that rVV-infected DC had very little ability to stimulate generation of IFN-g production by several Agspecific T-cell clones studied (unpublished observation).…”
Section: Effect Of Rvv-gp100 Infection On the Phenotype Of Idc And MDCmentioning
confidence: 83%
See 4 more Smart Citations
“…7,8,27 In particular, we observed that this strategy was more efficient than the exogenous pulsing of iDC with saturating levels of relevant epitope. 7,8 The reason for the enhanced efficiency remained unclear, and we postulated that the longer persistence of Ag on the surface of DC due to the prolonged production of antigenic molecules driven by the viral promoters might have been responsible. 8 Surprisingly, however, in the conduct of these studies we noted that rVV-infected DC had very little ability to stimulate generation of IFN-g production by several Agspecific T-cell clones studied (unpublished observation).…”
Section: Effect Of Rvv-gp100 Infection On the Phenotype Of Idc And MDCmentioning
confidence: 83%
“…In average 36.473.9% of iDC and 34.073.2% of mDC demonstrated expression of gp100 (Figure 1c), a figure similar to our previous experience using this infection protocol. 8 Cells demonstrating evidence of gp100 expression were separately gated and assessed for intensity of expression of the melanoma Ag. No significant differences were noted in intensity of gp100 expression between iDC and mDC (Figure 1d), nor with the constitutive level of expression of gp100 by the SK23 melanoma cell line (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations